The case of the baffled bear - Rylant, Cynthia; Karas, G. Brian ([New York] : b Greenwillow Books, 2004)
Bunny and Jack, animal detectives, take a break from playing cards to look for Bernard Bear$1 (Bs missing messenger whistle.s
Keywords: Animals -- Fiction; Mystery and detective stories